Crowned eagles rarely prey on livestock in central Argentina: persecution is not justified - Sarasola, José Hernán (2010)
Raptors have been reported to prey on livestock, causing considerable conflicts between birds of prey and local human communities. Previous studies have documented that human persecution is the most important threat to the endangered crowned eagle Harpyhaliaetus coronatus in central Argentina, due to a local belief that crowned eagles heavily and consistently prey on livestock. However, there are no empirical data supporting this assertion. Such information is crucial to evaluating possible measures to mitigate this human–wildlife conflict. We evaluated the feeding ecology of crowned eagles in semiarid habitats of central Argentina during the breeding seasons of 2002 to 2009. We also evaluated whether eagles are responsible for livestock predation and examined spatial-temporal variation in crowned eagles’ food habits. We identified 598 prey items consisting almost entirely of native prey: mammals (67.7%), reptiles (16.2%), birds (3.3%), fish (2.5%), and invertebrates (16.9%). We only recorded 1 (0.17%) occurrence of livestock prey remains, belonging to a domestic goat Capra hircus. Occurrences of the 4 main prey groups were not affected by habitat type or season. However, reptiles were recorded in higher numbers at sites where the diet of eagles was addressed by direct observation and video recording. Contrary to other human–predator conflicts worldwide, and assuming that the single livestock prey was not scavenged, our results show that crowned eagles rarely prey on livestock. We advocate reducing human–wildlife conflicts by implementing management and conservation measures and by educating local communities with respect to the ecological role of crowned eagles and other predators.